Experimental Measurement of the Adsorption Equilibrium and Kinetics of CO in Chromium-Based Metal-Organic Framework MIL-101 - Zhongzheng Zhang; Hui Wang; Jianyuan Li; Wei Wei; Yuhan Sun (Adsorption Science & Technology)
A series of MIL-101 samples with hierarchical pore structures and different surface areas (2000–4800 m 2 /g) was synthesized by hydrothermal method and characterized by X-ray diffraction, thermogravimetric analysis and 77-K N 2 adsorption isotherm. The adsorption equilibrium and kinetics of CO 2 were studied at 288, 298 and 308 K within a pressure range of 0–5 MPa by a volumetric method. The adsorption heat, mass-transfer constant, diffusion coefficient and diffusion activation energy were also investigated in this work. The results showed that the chromium-based MIL-101 adsorbent exhibited an impressive selectivity for CO 2 over N 2 and had an adsorption capacity of 20 mmol/g of CO 2 at 298 K and 5.0 MPa, which was much better than that of other conventional adsorbents (e.g. SBA-15, MCM-41, SG-A). The adsorption heat of CO 2 on MIL-101 was in the range of 21–45 kJ/mol, which decreased with the loading of CO 2 . The mass-transfer constants and diffusion coefficients increased with the temperature and decreased with the pressure, whereas the diffusion activation energy decreased with the increased pressure, indicating that adsorption of CO 2 at high pressures was easier. In addition, a linear correlation was found between CO 2 uptake and surface areas at low pressure, which showed that the adsorption capacity of CO 2 could be controlled by adjusting the surface area of the prepared adsorbents in this condition.